The Relationship Between Performance and Loneliness at Workplace: A Study on Academicians - Akçit, Volkan; Barutçu, Esin (European Scientific Journal, ESJ, 2017)
The objective of this study is to determine the relationship between workplace loneliness and performance. The sample of the study consists of 109 academicians in total, 64 males (58.7%) and 45 females (41.3%) who are working at Manisa Celal Bayar University. The study data were gathered through face-to-face and online questionnaires. Workplace loneliness scale by Wright, Burt and Strongman was used as a scale in the study. When the collected data were analyzed, it was found that there was a significant relationship between workplace loneliness and various demographic factors, while there was a negative relationship between workplace loneliness and performance.